To be, or not to be… registered:: a relational- phenomenological exploration of what State Registration means to psychotherapists - Evans, Ken; Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2009)
Little qualitative research has been carried out on psychotherapists’ perspectives on statutory regulation and the personal meanings they bring to bear to the current debate about professional registration. This research sets out to address this gap by exploring the lived experience of what state registration means to ten psychotherapists drawn from person-centred, gestalt and integrative approaches. A collaborative relational- phenomenological approach was undertaken using a focus group to collect data. Phenomenological and reflexive analysis highlighted the relevance and pervasive power of shame processes in four emergent themes: feeling pride-feeling shame, belonging-isolation, credibility-ineligibility and fight-flight. While formal regulation offers personal rewards around belonging, status and esteem, a shadow side lurks. Reflexive discussion suggests that unconscious parallel processes may be playing out in the wider professional arena.